2022
DOI: 10.3390/foods11172549
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanisms of the Potential Probiotic Lactiplantibacillus plantarum against Cardiovascular Disease and the Recent Developments in its Fermented Foods

Abstract: Cardiovascular disease (CVD) has become the leading cause of death worldwide. Many recent studies have pointed out that Lactiplantibacillus plantarum (Lb. plantarum) has great potential in reducing the risk of CVD. Lb. plantarum is a kind of lactic acid bacteria (LAB) widely distributed in fermented food and the human intestinal tract, some strains of which have important effects on human health and the potential to be developed into probiotics. In this review, we summarize the mechanism of potential probiotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 131 publications
0
6
0
Order By: Relevance
“…Studies have shown that polyphenols form stable complexes with enzymes through hydrogen bonding and hydrophobic interaction, thus reducing their catalytic activity. ( Zhang et al, 2018 , Wang et al, 2022 ) found that the inhibitory activity of persimmon fermented by flavobacterium and Lactobacillus plantarum on α-glucosidase was 2.06 ∼ 4.73 times that of the non-fermented group and the inhibitory effect on the α-glucosidase activity was highest at a fermentation time of 48–72 h.…”
Section: Functional Activities Of Fermented Fruit and Vegetable Juicementioning
confidence: 99%
“…Studies have shown that polyphenols form stable complexes with enzymes through hydrogen bonding and hydrophobic interaction, thus reducing their catalytic activity. ( Zhang et al, 2018 , Wang et al, 2022 ) found that the inhibitory activity of persimmon fermented by flavobacterium and Lactobacillus plantarum on α-glucosidase was 2.06 ∼ 4.73 times that of the non-fermented group and the inhibitory effect on the α-glucosidase activity was highest at a fermentation time of 48–72 h.…”
Section: Functional Activities Of Fermented Fruit and Vegetable Juicementioning
confidence: 99%
“…These benefits encompass not only the amelioration of gastrointestinal issues but also the potential to ameliorate metabolic syndrome, forestall CVD, bolster bone health, and contribute to cancer prevention (García‐Burgos et al., 2020; Sakandar & Zhang, 2021). Specifically, L. plantarum has been found to modulate human metabolism at the molecular, cellular, and population levels, leading to reduced blood glucose and lipids, regulated blood pressure, and ultimately decreased the incidence of CVD (Wang et al., 2022). Additionally, Limosilactobacillus fermentum exhibit antioxidant and anti‐inflammatory properties, effectively counteracting oxidative stress, inflammation, and diabetes (Lacerda et al., 2022).…”
Section: Addition Of Dietary Supplements—diversification Of Functions...mentioning
confidence: 99%
“…Thus, it has been associated with health benefits in bowel function, immune health, cardiovascular health, etc. [ 10 , 17 ]. However, L. plantarum is very sensitive to industrial processing, storage, and digestion, which markedly limits its use [ 10 ].…”
Section: Introductionmentioning
confidence: 99%